#### Answer

$$ G'(2)= -18.$$

#### Work Step by Step

Given $ G(x)=f(g(x))$, then we have $ G'(x)=f'(g(x))g'(x)$ and hence
$$ G'(2)=f'(g(2))g'(2)=f'(4)g'(2)=-2(9)=-18.$$

Chegg costs money, GradeSaver solutions are free!

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$$ G'(2)= -18.$$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.